Radical utu : critical ideas and ideals of Wangari Muta Maathai - Muhonja, Besi Brillian (Research in international studies. Africa series, 2020)
"Wangari Muta Maathai was a scholar-activist known for founding the Green Belt Movement, an environmental campaign that earned her the Nobel Peace Prize. While many studies of Maathai highlight her activism, few examine Maathai as a scholar whose contributions to various disciplines and causes spanned more than three decades. In 'Radical Utu : Critical Ideas and Ideals of Wangari Muta Maathai', Besi Brillian Muhonja presents the words and works of Maathai as theoretical concepts attesting to her contributions to gender equality, democratic spaces, economic equity and global governance, and indigenous African languages and knowledges. Muhonja's well-rounded portrait of Maathai's ideas offers a corrective to the one-dimensional characterization of Maathai typical of other works."--